2017 International Conference on Rehabilitation Robotics (ICORR) 2017
DOI: 10.1109/icorr.2017.8009223
|View full text |Cite
|
Sign up to set email alerts
|

Electromechanical delay in the tibialis anterior muscle during time-varying ankle dorsiflexion

Abstract: We evaluated the electromechanical delay (EMD) for the tibialis anterior (TA) muscle during the performance of time-varying ankle dorsiflexions. Subjects were asked to track a sinusoidal trajectory, for a range of amplitudes and frequencies. Motor unit (MU) action potential trains were identified from surface electromyography (EMG) decomposition and summed to generate the cumulative spike train (CST). CST and the exerted force were cross-correlated to identify the delay between the CST and force, which was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
4
1
Order By: Relevance
“…Unlike a previous study which observed that, for MVC levels lower than 10%, the EMD was longer when the MVC level was lower [ 24 ], the current study did not observe such an effect. It still remains unknown whether, at lower levels of MVCs, the ultrasound-detected onset would be dependent on MVC levels.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Unlike a previous study which observed that, for MVC levels lower than 10%, the EMD was longer when the MVC level was lower [ 24 ], the current study did not observe such an effect. It still remains unknown whether, at lower levels of MVCs, the ultrasound-detected onset would be dependent on MVC levels.…”
Section: Discussioncontrasting
confidence: 99%
“…This study detected a mean EMD of 73 ms, which is around half of that measured by Ubeda et al at 10% MVC in the same muscle [ 24 ]. This difference could be partly caused by the difference in positioning of the electrode, which can lead to 40–60 ms of error in EMD [ 25 ].…”
Section: Discussionmentioning
confidence: 54%
“…However, how the microstructures in the muscle combine to do so is less clear-the complexity and degree of linearity of the system are unknown. A representative example of a mechanism relevant for understanding the neuromechanics of muscle control is excitation-contraction coupling (E-C coupling), which is one of the components of the electromechanical delay (EMD)-a metric widely used to study human physiology (Cè et al 2014, Conchola et al 2015, Esposito et al 2016, Smith et al 2017, Úbeda et al 2017. E-C coupling refers to the communication between the electrical activity in the skeletal muscle fibre membrane and the release of calcium, eliciting the contraction (Calderón et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that electromechanical delay (EMD), which is typically defined as the time lag between electrical activation of a muscle and the onset of the exerted force (Cavanagh and Komi, 1979), is between 30 and 150 ms (Zhou et al, 1995; Blackburn et al, 2009; Nordez et al, 2009; Yavuz et al, 2010). Úbeda et al (2017) even found EMDs ranging from 112 to 361 ms. Considering that EMG appeared about 125 ms before force generation (Blackburn et al, 2009), the 170 ms time lag in our training system (which was caused by both the filter and the exoskeleton) is very short and acceptable.…”
Section: Discussionmentioning
confidence: 98%